A Family of Amphiphilic Cyclodextrin Liquid Crystals Governed by Dipole–Dipole Interactions. Issue 3 (14th December 2016) - Champagne, Pier‐Luc; Ester, David; Ward, Sandra; Williams, Vance E.; Ling, Chang‐Chun
Abstract: A novel family of amphiphilic cyclodextrin(CD)‐based liquid crystals that bear O ‐acetylated oligoethylene glycol chains at the secondary face is reported. Unlike most of the previously reported liquid crystals (LC) based on chemically modified CDs, which depend on H‐bonding as the primary intermolecular forces, the present CD derivatives self‐assemble into highly ordered smectic liquid crystal phases via the weaker dipole–dipole intermolecular interactions. The obtained materials are found to display much improved properties such as improved thermostability, reduced clearing temperatures, and better fluidity. The present work opens up new possibilities to design CD‐based LC materials. Abstract : Beyond hydrogen bonding : Amphiphilic cyclodextrin (CD)‐based liquid crystals have been synthesized that bear O ‐acetylated oligoethylene glycol chains at the secondary face and thioalkyl groups at the primary face. These compounds self‐assemble via dipole–dipole interactions to form highly ordered smectic liquid crystal phases with useful properties.